2004
DOI: 10.1523/jneurosci.5426-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dominant Rhodopsin Mutation Triggers Two Mechanisms of Retinal Degeneration and Photoreceptor Desensitization

Abstract: A variety of rod opsin mutations result in autosomal dominant retinitis pigmentosa and congenital night blindness in humans. One subset of these mutations encodes constitutively active forms of the rod opsin protein. Some of these dominant rod opsin mutant proteins, which desensitize transgenic Xenopus rods, provide an animal model for congenital night blindness. In a genetic screen to identify retinal degeneration mutants in Drosophila, we identified a dominant mutation in the ninaE gene (NinaE pp100 ) that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…G␣ q Mutant Undergoes Slow Retinal Degeneration-Mutations in almost any gene that functions during phototransduction trigger rapid retinal degeneration, except the G␣ q 1 mutant, which undergoes slow retinal degeneration (34,43,44). In this study, we showed that the G␣ q 961 mutant undergoes slow lightdependent retinal degeneration, similar to that observed in the G␣ q 1 mutant (44).…”
supporting
confidence: 67%
“…G␣ q Mutant Undergoes Slow Retinal Degeneration-Mutations in almost any gene that functions during phototransduction trigger rapid retinal degeneration, except the G␣ q 1 mutant, which undergoes slow retinal degeneration (34,43,44). In this study, we showed that the G␣ q 961 mutant undergoes slow lightdependent retinal degeneration, similar to that observed in the G␣ q 1 mutant (44).…”
supporting
confidence: 67%
“…Furthermore, a previous study has shown that the constitutively active rhodopsin mutant ninaE pp100 causes a stable association of the photopigment to Arr2 and thereby reduces the sensitivity to light by Ͼ10-fold (Iakhine et al, 2004). To examine the involvement of photopigment internalization in long-term adaptation, we examined whether photopigment phosphorylation plays a role in long-term adaptation.…”
Section: The Photopigment Cycle Is Not Involved In Long-term Adaptationmentioning
confidence: 99%
“…Constitutive or uncontrolled activity of rhodopsin can also lead to retinal degeneration, such as in the dominant allele, NinaE PP100 [222]. This retinal degeneration is partially suppressed by mutations in arr2 or Gα q , whereas complete suppression is achieved by disrupting both arr2 and the Gα q .…”
Section: Retinal Degenerationmentioning
confidence: 99%